Analysis of Human Resources and IT Infrastructure Readiness in the Implementation of the Electronic Medical Record System at the UPT Puskesmas Rawat Inap Lolofitu Moi - Marbun, William Jhonson; Mendrofa, Syah Abadi; Halawa, Odaligoziduhu; Telaumbanua, Eliagus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the readiness of human resources (HR) and information technology (IT) infrastructure in supporting the implementation of the Electronic Medical Record System (EMR) at the UPT Puskesmas Rawat Inap Lolofitu Moi. The background of this research is grounded in the importance of digital transformation in the healthcare sector and the obligation for health facilities to adopt EMR systems as stipulated in national regulations. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation with key informants, including the head of the health center, medical record officers, and the head of administration. The findings reveal that HR readiness is in the